Competitive storytelling: What do teachers do in assisting students to win the contest? - Mulyadi Syahputra (English Education Journal, 2022)
This study was aimed to investigate the teachers’ strategy used by the teachers in assisting their students to win story telling contests. The study employed the qualitative approach with multiple case study as the design. The teachers from five schools considered as the role model based on the number of their students’ achievement in storytelling contest were interviewed. The data were then analyzed by data condensation, data display and conclusion (Miles, Huberman, Saldana, 2018). The conclusion of the study illustrated that the preparation process conducted by those teachers were motivation through emphasizing the benefit of joining the storytelling contest, providing a role model of a successful storyteller, enabling the parents approach to strengthen the benefit of storytelling to the students, avoiding a winning oriented competition that put more burden to their shoulders, and facilitating internal competitions. Moreover, the result found that the coaching strategy used by the teachers were adjusting duration, reading the story, modelling, observing, and giving feedback. Lastly, the sources of storytelling model that the teachers used were also available.